2017
DOI: 10.1088/1361-648x/aa58bc
|View full text |Cite
|
Sign up to set email alerts
|

Confinement of vibrational modes within crystalline lattices using thin amorphous layers

Abstract: It is possible to confine vibrational modes to a crystal by encapsulating it within thin disordered layers with the same average properties as the crystal. This is not due to an impedance mismatch between materials but, rather, to higher order moments in the distribution of density and stiffness in the disordered phase-i.e. it is a result of material substructure. The concept is elucidated in an idealized one-dimensional setting and then demonstrated for a realistic nanocrystalline geometry. This offers the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Wan et al 7 incorporated Yb 3+ ions into the pyrochlore-type La 2 Zr 2 O 7 and observed a pronounced ''rattler'' effect, leading to a significant reduction in k. Recently, a high-entropy strategy has been employed to maximize lattice disorder to further reduce k. [8][9][10][11] The k of defective high-entropy oxides can present an almost temperature-independent glass-like behavior with a value approaching the theoretical minimum limit, k min . 12 This glass-like behavior 7,[13][14][15][16][17][18] requires a more comprehensive understanding of phonon heat transport in defective crystals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wan et al 7 incorporated Yb 3+ ions into the pyrochlore-type La 2 Zr 2 O 7 and observed a pronounced ''rattler'' effect, leading to a significant reduction in k. Recently, a high-entropy strategy has been employed to maximize lattice disorder to further reduce k. [8][9][10][11] The k of defective high-entropy oxides can present an almost temperature-independent glass-like behavior with a value approaching the theoretical minimum limit, k min . 12 This glass-like behavior 7,[13][14][15][16][17][18] requires a more comprehensive understanding of phonon heat transport in defective crystals.…”
Section: Introductionmentioning
confidence: 99%
“…8–11 The κ of defective high-entropy oxides can present an almost temperature-independent glass-like behavior with a value approaching the theoretical minimum limit, κ min . 12 This glass-like behavior 7,13–18 requires a more comprehensive understanding of phonon heat transport in defective crystals.…”
Section: Introductionmentioning
confidence: 99%